Object-oriented development process and metrics - De Champeaux, Dennis (Prentice Hall, 1997)
"In this text, Dennis de Champeaux clearly presents the practical basics of each phase of the software development life-cycle using an object-oriented analysis and design process. A detailed home heating system is effectively used as an example throughout the text to instruct project managers, software developers, and researchers how to transform from an analysis via design into an implementation." "The author uses state-of-the-art techniques to identify detailed software development micro processes to help manage projects and schedules. In addition, discussions are included on following micro processes, how effort prediction can be done, and how effort metrics can be applied to systematically collect historical data."--BOOK JACKET.